THE MANIFESTATION OF SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF COPING BEHAVIOR STRATEGIES AMONG STUDENT YOUTH - Sultankulova Gulnara Furkatjon kizi (American Journals Publishing, 2025)
This article analyzes the relationship between the psychological views of foreign psychologists in this regard, draws conclusions based on the results of research conducted in the field of protective mechanisms for student youth in extreme situations and the manifestation of coping behavior.
Keywords: Coping behavior, coping strategy, overcoming, defense mechanism,